Porsi Konsumsi Sayur dan Buah Signifikan Menurunkan Asupan Energi: Sistematik Review - Nursalim .; Chaerunnimah .; Abdullah Thamrin; Dien Abdul Munir; Sirajuddin . (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
AbstractBackground of this study is that controlling body weight is one of them by increasing the consumption of vegetables and fruit, because it has a lower energy content than other food ingredients such as energy sources (staple foods and side dishes).Objective of this study was to determine the amount of vegetable and fruit intake that can reduce energy intake.Method is a systematic review by tracing various studies related to vegetable and fruit consumption on various search engines, namely PubMed, Scinapse, Nature. The search term used is